The characteristics of a modern oxy-fuel power plant - Kotowicz, Janusz; Michalski, Sebastian; Brzęczek, Mateusz (MDPI, 2019)
This paper presents the thermodynamic and economic analyses of four variants of a supercritical oxy-type plant. These variants differed in terms of air separation units (ASU, variants: V1—cryogenic; V2—hybrid; equipped with a three-end (V3a) or four-end (V3b) high-temperature membrane) and boilers (V1 and V3a—lignite-fired fluidized-bed; V2 and V3b—hard-coal-fired pulverized-fuel). The gross power of steam turbine unit (STU) was 600 MW. The live and reheated steam parameters were 650 °C/30 MPa and 670 °C/6.5 MPa, respectively. The influence of the ASUs’ operating parameters on the ASUs’ auxiliary power rate and boiler efficiency (V3a and V3b only) was studied. The ASUs’ operating parameters for maximum net efficiency were then determined. The decrease in the net efficiency compared to a reference plant (with a classic fluidized-bed or pulverized-fuel boiler) fluctuated in the range 7.2 (V3b)–11.2 (V1) p.p. An analysis of the waste heat utilization was performed (fuel drying—V1 and V3a; STU steam-water heat exchangers replacing). Thus, the efficiency decreases fluctuated in the range 4.3 (V3b)–10.2 (V1) p.p. The economic analysis showed that in order for the variants to be economically viable, the unit CO2 emission cost should be greater than 42.2 (V1) or 22.0 (V3b) EUR/MgCO2.
Keywords: oxy-fuel power plant; air separation unit; CO2 capture unit; CO2 compression unit; clean energy